Perlindungan Hukum Seorang Anak Sebagai Pemohon Dispensasi Kawin Pasca Revisi Undang-Undang Perkawinan - Putra, Yoga Abiansyah Dwi; Yunanto, Yunanto (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
In general, those who apply for a marriage dispensation are the parents or guardians of the child as in Article 7 paragraph (2) of Law No. 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, when the petitioner are often minors where they are legally incompetent. This study aims to find out how the legal protection of minors as a marriage dispensation petitioner after the revision of the Marriage Law and the judge's efforts in determining the marriage dispensation application where the Petitioner is a child. The research method used is a normative juridical approach with library research data collection techniques from secondary data and field studies using interview techniques from primary data. The results of the study indicate that legal protection for minors as petitioner for marriage dispensation after the revision of the Marriage Law has not been maximized because there is still a legal void, it is necessary to make written rules from the government that can guarantee legal certainty. Efforts that can be made by judges to determine cases of this kind are judges making legal discoveries while still prioritizing the best interests for children.